Not my girl - Jordan-Fenton, Christy; Pokiak-Fenton, Margaret-Olemaun, 1936- (Annick Press, 2014)
Margaret can<U+2019>t wait to see her family, but her homecoming is not what she expected. Based on the true story of Margaret Pokiak-Fenton, and complemented by evocative illustrations, Not My Girl makes the original, award-winning memoir, A Stranger at Home, accessible to younger children. It is also a sequel to the picture book When I Was Eight. A poignant story of a determined young girl<U+2019>s struggle to belong, it will both move and inspire readers everywhere.